Prospects for Christian Spiritual Development in Higher Education - Karaliūtė, Aušra (Acta Paedagogica Vilnensia, 2001)
The Jaws of the Republic of Lithuania determine moral formation as an integral part of general education. At present only those majoring in religious studies have this possibility among the 64,000 students in 15 institutes of higher education and 34,000 in 70 professional schools of junior colleges. The author’s research of 700 first-, second- and third-year students lists religious preference, religious practice (77 % are baptized, 60 % participate in church services at least occasionally), and opinion regarding religious studies in universities. One-third are in favour of integral programs, the majority favour elective courses: 27 % would attend spirituality courses, 19 % Scripture study, 19 % Christian ethics. The Ministry of Vilnius University’s St. John’s church pastoral team is described.